Research trends in social media addiction and problematic social media use: A bibliometric analysis - Pellegrino, Alfonso; Stasi, Alessandro; Bhatiasevi, Veera (Frontiers in Psychiatry, 2022)
Despite their increasing ubiquity in people’s lives and incredible advantages in instantly interacting with others, social media’s impact on subjective well-being is a source of concern worldwide and calls for up-to-date investigations of the role social media plays in mental health. Much research has discovered how habitual social media use may lead to addiction and negatively affect adolescents’ school performance, social behavior, and interpersonal relationships. The present study was conducted to review the extant literature in the domain of social media and analyze global research productivity during 2013 to 2022. Bibliometric analysis was conducted on 501 articles that were extracted from the Scopus database using the keywords social media addiction and problematic social media use. The data were then uploaded to VOSviewer software to analyze citations, co-citations, and keyword co-occurrences. Volume, growth trajectory, geographic distribution of the literature, influential authors, intellectual structure of the literature, and the most prolific publishing sources were analyzed. The bibliometric analysis presented in this paper shows that the US, the UK, and Turkey accounted for 47% of the publications in this field. Most of the studies used quantitative methods in analyzing data and therefore aimed at testing relationships between variables. In addition, the findings in this study show that most analysis were cross-sectional. Studies were performed on undergraduate students between the ages of 19-25 on the use of two social media platforms: Facebook and Instagram. Limitations as well as research directions for future studies are also discussed.